Pengaruh Pelatihan Kerja Terhadap Peningkatan Produktivitas Kerja Karyawan Bandar Udara Radin Inten II Lampung - Suwandi SUWANDI (SOSIALITA, 2011)
At the level of national and international, the development of air transportation business at present shows encouraging prospective. It is characterized by the increasing number of scheduled airlines and the increasing frequency of flights at airports in Indonesia. In line with the natural conditions of Indonesia in which consist of thousands of islands, the air transportation has become the primary choice compared with other modes of transportation (sea and land) as the air transportotation has the advantages in term of a faster time and the convenience for the users who obtained the services. Airport as an element in the operation of aviation has a very important and strategic so that its implementation is controlled by the State and the sustainibilty is done by the government with a view to realize the safe, secure, smooth, orderly, comfortable, efficient, and equitable aviation organization, to support the growth and stability as the driving and supporting factors the national development. The formulation of the problem in this the research is to figure out whether there is a relationship between job training with work productivity of employees in the Raden Inten II Airport, and whether there is job training effects on the productivity of employees working in Bandar Lampung II Air Raden Inten Airport. After researchers conducted a study of a predetermined object , researchers can discuss and conclude that there is a positive relationship between job training with employee productivity in Airport Raden Inten II Lampung as it is seen from the results of 0.464 count r> r tables of both the tarafikan 5% 0.281 and the level of closeness relations is middle. Qualitatively, the implementation of job training and productive employees in Lampung Raden Inten II Airport falls in the very good category, the productivity of employees who followed the training at a moderate level with the average value of 3.16 of a scale of 5. This productivity is demonstrated by the speed of task completion, low level Â errors, work neatness, better quantity results, improved discipline, cooperation. The influence of training on work productivity employees of Lampung Raden Inten II Airport is 21.53%. The remaining of 78.47% influenced by other factors.Dan institutional advice Airport Radin Inten II in order to create job training programs are scheduled with a good and sustainable, the material given in the training should be based on participant needs and adapted to the burden of duties and responsibilities.The institutional advice given to Radin Inten II Airport is to make the scheduled and continously job training programs. The material given in the training should be based on the participant needs and adapted based on to their duties and responsibilities.